MOPEDS: Motorized Objects Propelling Ethanol Drinking Subjects - Christmas, A. Britton; Brintzenhoff, Rita A.; Schmelzer, Thomas M.; Head, Karen E.; Sing, Ronald F. (The American surgeon, 2011)
Mopeds are not subject to the same laws and jurisdiction as cars or motorcycles, including the requirement of a driver's license. We undertook this study to examine the influence of alcohol (ETOH) on moped crashes. We retrospectively reviewed adult moped injuries compared with motor vehicle crashes (MVCs) and motorcycle crashes (MCCs) from 1995 through 2006. Demographics, severity of injury, mortality, and serum ETOH levels were recorded. Data were analyzed using the Student t test for continuous data and the χ 2 test for proportional data. Motor vehicle crashes accounted for 7186 admissions. MCC and moped crashes numbered 973 and 113, respectively. Although not statistically significant ( P = 0.064), moped crashes yielded the highest mortality (9.7%) compared with MCCs (8.5%) and MVCs (6.7%). An increased association of blood ETOH levels with moped crashes, however, was statistically significant ( P = 0.004). Serum ETOH levels above 0.05 g/dL were observed in 1681 MVCs (23.4%), 241 MCCs (24.8%), and 44 moped crashes (39%). In this study, we discovered that moped crashes demonstrate a significantly higher ETOH involvement than either MVCs or MCCs representing a previously unrecognized public safety risk.